1991
DOI: 10.1111/j.1471-4159.1991.tb02026.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Quantitation of the β‐Amyloid Precursor Protein in the Cerebrospinal Fluid of Alzheimer's Disease Patients with a Monoclonal Antibody‐Based Immunoassay

Abstract: One of the major clinical findings in Alzheimer's disease (AD) is the formation of deposits of beta-amyloid protein in amyloid plaques, derived from the beta-amyloid precursor protein (beta-APP). To determine the possible use of beta-APP as a diagnostic marker for AD in CSF, a monoclonal antibody-based immunoassay specific for this protein was developed. The assay does not differentiate between beta-APP695 and beta-APP751 forms but does preferentially recognize beta-APP751 complexed with a protease. Of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 36 publications
2
15
1
Order By: Relevance
“…Our immunoblotting pattern, which appears as a single APP species, differs from previous studies that have reported two distinct APPs (Kunitz protease inhibitor domaincontaining and -lacking forms) in CSF (17)(18)(19)(20)(24)(25)(26). mAb P2-1 recognizes forms of APP that contain or lack the Kunitz protease inhibitor domain (32).…”
Section: Resultscontrasting
confidence: 82%
See 2 more Smart Citations
“…Our immunoblotting pattern, which appears as a single APP species, differs from previous studies that have reported two distinct APPs (Kunitz protease inhibitor domaincontaining and -lacking forms) in CSF (17)(18)(19)(20)(24)(25)(26). mAb P2-1 recognizes forms of APP that contain or lack the Kunitz protease inhibitor domain (32).…”
Section: Resultscontrasting
confidence: 82%
“…Our results show a more pronounced decrease in CSF APP levels in AD patients than have other recent reports (25,26). To understand the basis for these differences, we conducted parallel ELISA studies on purified PN-2[APP] and representative CSF samples using our mAb P2-1 and mAb 22C11, which was used in one of the other studies (25).…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…For the detection of secreted APP, the monoclonal antibody 1G5 [29] was used, and the blots were incubated overnight at room temperature. Detection was carried out by incubation with horseradish peroxidase-conjugated goat antimouse IgG (Kirkegaard and Perry Laboratories, Gaithersburg, MD, U.S.A.) for 1 h. The blots were then washed extensively and sAPP visualized using an enhanced chemiluminescence method (Amersham).…”
Section: Immunodetection Of Sappmentioning
confidence: 99%
“…Immunoblots were probed with (i) affinitypurified rabbit antibodies to bacterially expressed recombinant proteins of either jAPP4"_592 [aB5 (14); numbering according to BAPP695 (5) Ihara, Tokyo University). A monoclonal antibody to recombinant BAPP"44592 (1GS) has been described (18). Two antibodies to APP were used: a high-titer rabbit antiserum (1280) to synthetic AfBP1_40, produced as described (19) for our antiserum Y to Af3P1-38, and a monoclonal antibody (6C6) to synthetic AiP1_28, from D. Schenk (Athena Neurosciences).…”
mentioning
confidence: 99%